L’irrequietezza come scelta - Crouch, Colin (SocietàMutamentoPolitica, 2019)
The essay traces the complex path of a high-profile intellectual who has profoundly innovated European sociological thought. Ralf Dahrendorf’s “restlessness” is the basis of a continuous transition between different and distant countries and universities and of his wise oscillation between study and politics, between scientific analysis and diagnosis of contemporaneity. A careful biographical reconstruction is followed by a critical presentation of his extraordinary contribution on four interdependent intellectual and normative themes: the rejection of utopia and homo sociologicus, the passionate acceptance and reflection on conflict, the exploration of entitlements and provisions, options and ligatures. A significant portrait emerges that underlines the tension between his social theory, or rather, a conception of sociology that constantly avoids formal abstraction because it considers the person in his full humanity and his orientations as a liberal democrat at the centre of his interest. His firm neo-liberal conviction, however, has never stifled his social-democratic instincts of family origin. The moral action that guided Dahrendorf in his public life as a European scientist and politician never made him ein großer Ordinarius but always ein großer Mensch.